THE IMPLEMENTATION OF THE PRINCIPLE OF TRANSFERENCE IN DETERMINATION OF THE BUDGETS IN THE LEGISLATIVE MECHANISM OF SOUTH SULAWESI - -, Mustawa (Journal of Humanity, 2013)
Regulations of the province of South Sulawesi provincial tertip no. 17 of 2004, which became the basis of the implementation of budget revenue assignment mechanism Government Regulations area 2005 South Sulawesi province turned out not to Government Regulationsthe implementation of the principle of transparency. Because none of the regulatory charge lighting material which requires tertip transparency in the establishment of national mechanisms in 2005. The mechanism of the grant budgetÂ 2005 in the south sulawesi provincial government does not comply with the principle of transparency which is set in the context of the law of the country, in particular those provided for in article 23 paragraph 1 of chapter vii of the constitution of 1945 which confirmed, budget revenues and state spending as a form of state financial management are set each year by law and carried out in an open and responsible for the most of peoples prosperity